KEANEKARAGAMAN JENIS-JENIS ANGGREK DI CAGAR ALAM KOFIAU KABUPATEN RAJA AMPAT - P Ponisri; Lona H. Nanlohy (JURNAL GALUNG TROPIKA, 2021)
This study aims to determine the abundance of orchid species, diversity, evenness and dominance of orchid species in the Kofiau Nature Reserve, Raja Ampat Regency. This forest area is a habitat for various endemic flora and fauna, including orchids. Orchid is one of the seed plants of the Orchidaceae family which is in great demand because of its attractive flower shape and color so that it can be used as raw material for the cut flower industry, potted plants or garden decorations. The procedure used in this study was field observation/exploration technique, the determination of the observation sample was carried out by considering the area objectively overgrown with orchids. charts, graphs and photos). Based on the results of exploration and identification of orchid species in the Kofiau Nature Reserve, there are 3 types of epiphytic orchids and 1 type of terrestrial/soil orchid, so the total number is 4 types of orchids, consisting of 1 genus of soil orchid (Spathoglotis) and 3 genera of epiphytic orchids, namely Dendrobium. 2 species and Grammathophyllum 1 species. With the highest number of individuals, Grammatophylum scriptum 128 (50.00%), then Spathoglotis plicata with the highest number of individuals, 107 (41.797%), this is the highest number of orchids found in mangrove forests, then Dendrobium allofolium with 15 individuals. (5.859%), and D. crumenatum with 6 individuals (2.344%) with a total of 256 orchid individuals found in mangrove forests. The orchid species diversity index value is 0.3771 and the dominance index is 0.4287 and the evenness index value is 0.0943. Where the index value of diversity and species dominance on orchids in the Nature Reserve forest is in the low category while the evenness index value is in the medium category.